Model based prediction of the trap limited diffusion of hydrogen in post‐hydrogenated amorphous silicon. Issue 11 (14th October 2016) - Gerke, Sebastian; Becker, Hans‐Werner; Rogalla, Detlef; Job, Reinhart; Terheiden, Barbara
Abstract : The diffusion of hydrogen within an hydrogenated amorphous silicon (a‐Si:H) layer is based on a trap limited process. Therefore, the diffusion becomes a self‐limiting process with a decreasing diffusion velocity for increasing hydrogen content. In consequence, there is a strong demand for accurate experimental determination of the hydrogen distribution. Nuclear resonant reaction analysis (NRRA) offers the possibility of a non‐destructive measurement of the hydrogen distribution in condensed matter like a‐Si:H thin films. However, the availability of a particle accelerator for NRR‐analysis is limited and the related costs are high. In comparison, Fourier transform infrared spectroscopy (FTIR) is also a common method to determine the total hydrogen content of an a‐Si:H layer. FTIR spectrometers are practical table‐top units but lack spatial resolution. In this study, an approach is discussed that greatly reduces the need for complex and expensive NRR‐analysis. A model based prediction of hydrogen depth profiles based on a single NRRA measurement and further FTIR measurements enables to investigate the trap limited hydrogen diffusion within a‐Si:H. The model is validated by hydrogen diffusion experiments during the post‐hydrogenation of hydrogen‐free sputtered a‐Si. The model based prediction of hydrogen depth profiles in a‐Si:H allows more precise design of experiments, prevents misinterpretations, avoids unnecessary NRRA measurements and thus saves time and expense. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Nuclear resonant reaction analysis (NRRA) enables to measure the hydrogen distribution within condensed matter like hydrogenated amorphous silicon (a‐Si:H). Therefore, a particle accelerator is needed making NRR‐analysis complex and cost intensive. Using physical relationships, an advanced diffusion model enables to predict hydrogen depth profiles mainly on the base of Fourier transform infrared (FTIR) measurements. This allows more precise design of experiments, avoids unnecessary NRRA measurements and thus saves time and expense.